1973
DOI: 10.1126/science.181.4102.873
|View full text |Cite
|
Sign up to set email alerts
|

Clarification of the Chemical Status of the Pink Bollworm Sex Pheromone

Abstract: Propylure, 10-n-propyl-trans-5,9-tridecadienyl acetate, and deet, N,N,-diethyl-m-tolumide, were previously reported as the sex pheromone and a sex pheromone activator, respectively, of the pink bollworm. Neither chemical in three extracts of female moth abdomen tips could be detected by gas-liquid chromatographic analysis. These compounds, alone or in combination, exhibited little or no biological activity in the laboratory or in the field. Hexalure, cis-7-hexadecenyl acetate, a synthetic attractant for pink b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

1976
1976
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(47 citation statements)
references
References 13 publications
0
46
0
1
Order By: Relevance
“…Hummel et al, (1973) identified a mixture of the Z,Z-and Z,E-isomers of 7,11-hexadecadienyl acetate as the pink bollworm sex pheromone and proposed the name "gossyplure." Shorey et al, (1976) initiated studies to evaluate the mating disruption method, in which the atmosphere of the cotton field was permeated with gossyplure, for PBW control.…”
Section: Various Methods Of Pbw Controlmentioning
confidence: 99%
“…Hummel et al, (1973) identified a mixture of the Z,Z-and Z,E-isomers of 7,11-hexadecadienyl acetate as the pink bollworm sex pheromone and proposed the name "gossyplure." Shorey et al, (1976) initiated studies to evaluate the mating disruption method, in which the atmosphere of the cotton field was permeated with gossyplure, for PBW control.…”
Section: Various Methods Of Pbw Controlmentioning
confidence: 99%
“…Later studies (57) showed that although (4) was present in extracts, the active material was (536) (see p. 10). Similarly, the sex pheromone of the pink boll worm moth (Pectinophora gossypiella) was first reported as (5) with synthetic material active in the laboratory (78) and later (79) shown to be a mixture of Z,Z-and Z,E-isomers of 7,11-hexadecadienyl acetate (529a and 529b, respectively). A number of other sex pheromones have been misidentified,.…”
Section: Problemsmentioning
confidence: 97%
“…The most attractive ratio of (Z,Z)-and (Z,E)-7,1l-hexadecadienyl acetate (529a and 529b; Scheme 91) for the pink boll worm, Pectinophora gossypiella, was claimed to be 1 : 1 (79,233). ROTHSCHILD (286) found that three species, P. gossypiella, P. endema and P. scutigera, were maximally attracted to ratios of 1 : 1, 1: 0.5 and 1: 0.1 Z,Z, to Z,E and indicated that these ratios may provide a mechanism for reproductive isolation.…”
Section: A Geometric Isomersmentioning
confidence: 99%
“…However, the synthetic replicas of the natural attractants are already available for many of the Nation's more important insect pests. They include: cabbage looper, Trichoplusia ni (Hubner), (1); boll weevil, Anthonomus grandis Boheman (2,3); gypsy moth, Porthetria dispar (Linnaeus), (4); pink bollworm, Pectinophora gossypiella (Saunders), (5); tobacco budworm, Heliothis virescens (Fabricus), (6); European corn borer, Ostrinia numilalis (Hubner), (7); codling moth, Laspeyresia pomonella (L), (8,9); several species of bark beetles attacking forest trees (10-13); Douglas-fir tussock moth, Hemerocampa pseudotsugata McDonnough (formerly called Ogyia pseudotsugata), (14); and house fly, Musca domestica (L.), (15).…”
Section: Available Pheromones and Kairomonesmentioning
confidence: 99%